2013
DOI: 10.19070/2328-353x-1300026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Infections on Serum Creatinine Levels in Diabetic Rats

Abstract: Aim:The aim of this study was to evaluate the relationship between pulpal and/or periodontal disease and serum creatinine levels in a rat model of diabetes mellitus.Methods: Eighty male rats (Rattus norvegicus albinus, Wistar) were divided into the following 8 groups compris-ing 10 animals each: normal (G1), with pulpal disease (G2), with periodontal disease (G3), with both pulpal and periodontal disease (G4), diabetic (G5), diabetic with pulpal disease (G6), diabetic with periodontal disease (G7), and diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Thus, they concluded that the increase in serum CK level might indicate a compromised oral health status [45]. The results are in the same direction as Cintra et al results, who found that increase in serum creatinine is related to gingival damage due to oral infections [46]. Also, the result of the study is in agreement with Yoshihara et al finding, who observed relation of gingival and periodontium tissue damage with creatinine level [47].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, they concluded that the increase in serum CK level might indicate a compromised oral health status [45]. The results are in the same direction as Cintra et al results, who found that increase in serum creatinine is related to gingival damage due to oral infections [46]. Also, the result of the study is in agreement with Yoshihara et al finding, who observed relation of gingival and periodontium tissue damage with creatinine level [47].…”
Section: Discussionsupporting
confidence: 87%